Study of sensitivity and specificity of five rapid plasmareagin test kits in syphilis - Shrestha, B (Journal of Institute of Medicine Nepal, 2007)
Background: Syphilis caused by Treponema pallidum has been associated with humankind since ancient times. Materials and Methods: Blood samples from 408 healthy Nepalese male population was collected and tested to find out the sensitivity and specificity of five different (a, b, c, d and e) non-treponemal syphilis serological test rapid plasma reagin (RPR) as well as for the screening of the healthy target group for syphilis. Results: Six subjects (1.47%) were found positive with the test and by Treponema pallidum Haemagglutination (TPHA) test was identified as a syphilitic subject. With the test kits a, c and d 34 false positive cases were detected. The sensitivity was 100%, and the specificity was 92% only. Whereas with test kits b and e only six true positive cases were detected thus making their sensitivity and specificity 100%. Conclusion: Therefore, it is concluded that test kits a, c and d should only be used for the screening purpose. On the other hand, the test kits b and e can be used for the diagnostic purpose. Key words: RPR, TPHA, syphilis, sensitivity, specificity The full text of this paper is available at Journal of Institute of Medicine website